The Pentateuch on the XXI. Century: Retrospective and prospects - Monteiro, Sérgio (Vox Scripturae - Revista Teológica Internacional, 2015)
This article describes the current crisis in Pentateuch research, presenting its origin and results, as well as the impact on the modern research. It shows the main players in the debate and its contribution to the current status in the field. It finishes describing the future of the research, as we can grasp from the current research and the trend it has taken.
Keywords: Pentateuch; Research on the Pentateuch; Exegesis of the Pentateuch